Blowing people's minds: Anarchist thought in Dambudzo Marechera's mindblast - Mutekwa, Anias (James Currey, 2021)
Reading Marechera’s work encourages one to look again at the political philosophy of anarchism. Like Marxism, against which it was conceived, anarchism represents one of those liberatory discourses that were in one way or another linked with the Enlightenment. Its leading proponents were Kropotkin and Bakunin in Russia, Proudhon in France, and Godwin in England. As Pierre-Joseph Proudhon makes clear in his writings, anarchists are opposed to all forms of power, authority and hierarchy.¹ Indeed, one of the defining features of nineteenth-century European anarchism was the way in which the State was regarded as the major source of repression. Unsurprisingly then, Proudhon and others sought its abolition. Privileging the freedom of the individual, whose instincts and intuitions need to be given free expression rather than limited by the demands and exigencies of the State, anarchism proposes: Liberty that consists in the full development of all the material, intellectual and moral powers that are latent in each person; liberty that recognizes no restrictions other than those determined by the laws of our own individual nature, which cannot properly be regarded as restrictions since these laws are not imposed by any outside legislator beside or above us, but are immanent and inherent, forming the very basis of our material, intellectual and moral being … they do not limit us but are the real and immediate conditions of our freedom.